Ectopic Pregnancy and Prenatal Diagnosis - Wu, Wei; Tang, Qiuqin; Tsikouras, Panagiotis; Rath, Werner; Von Tempelhoff, Georg-Friedrich; Nikolettos, Nikolaos (IntechOpen, 2022)
Ectopic pregnancy is an implantation occurring elsewhere than in the cavity of the uterus. It is the leading cause of maternal morbidity and mortality during the first trimester. While the incidence of extrauterine pregnancy has increased in recent years, the rapid development of multi-omics has also provided an effective method of prenatal diagnosis. This book focuses on the diagnosis and treatment of ectopic pregnancy, fetal malformation, and the different screening methods for prenatal diagnosis.